Antiviral role of nanomaterials: a material scientist's perspective. Issue 1 (21st December 2022) - Aanish Ali, Muhammad; Rehman, Nagina; Park, Tae Joo; Basit, Muhammad Abdul
Abstract : An overview of applications of nanoparticles and their combinations with a variety of antiviral drugs. Abstract : The present world continues to face unprecedented challenges caused by the COVID-19 pandemic. Collaboration between researchers of multiple disciplines is the need of the hour. There is a need to develop antiviral agents capable of inhibiting viruses and tailoring existing antiviral drugs for efficient delivery to prevent a surge in deaths caused by viruses globally. Biocompatible systems have been designed using nanotechnological principles which showed appreciable results against a wide range of viruses. Many nanoparticles can act as antiviral therapeutic agents if synthesized by the correct approach. Moreover, nanoparticles can act as carriers of antiviral drugs while overcoming their inherent drawbacks such as low solubility, poor bioavailability, uncontrolled release, and side effects. This review highlights the potential of nanomaterials in antiviral applications by discussing various studies and their results regarding antiviral potential of nanoparticles while also suggesting future directions to researchers.